Eksplorasi Penerapan Green Marketing untuk Membangun Keunggulan Kompetitif pada Pelaku UMKM Perempuan - Margareta Ernanda Rahardani; Vincentia Indah Puspitasari (Jurnal Maksipreneur, 2026)
Micro, small, and medium enterprises (MSMEs) represent a vital driver of Indonesia’s economic growth, with women comprising 64.5% of business actors. In Surakarta, a tourism-oriented city with 13,203 active MSMEs in 2023, women entrepreneurs hold significant potential to strengthen competitiveness. However, increasing environmental challenges demand greater adoption of sustainable practices. This study investigates the role of green awareness and green knowledge in enhancing competitive advantage through green marketing among women-led MSMEs in Surakarta. A quantitative method was applied using questionnaires distributed to 100 respondents, with data analysed through SEM-PLS. The results demonstrate that green knowledge significantly affects competitive advantage, both directly and indirectly through green marketing. In contrast, green awareness does not show a significant influence on competitive advantage, nor through green marketing mediation. These findings highlight the strategic importance of knowledge-based approaches in fostering sustainable competitiveness for women entrepreneurs.